An experimental study of compressive toughness of Steel–Polypropylene hybrid Fibre-Reinforced concrete. (March 2022) - Alwesabi, Emad A.H.; Abu Bakar, B.H.; Alshaikh, Ibrahim M.H.; Abadel, Aref A.; Alghamdi, Hussam; Wasim, Muhammad
Highlights: The effect of PF + MSF hybridization on the compressive toughness of FRC has been examined; The highest compressive toughness has been reported for 0.1% PF + 0.9% MSF hybrid fiber in concrete; The substitution of MSF with PF, which exceeded 0.1%, reduced compressive strength, as well as the compressive toughness characteristics of concrete; The hybrid 0.9% MSF-0.1% PF reported the highest compressive strength with reduced water absorption and voids in concrete. Abstract: The hybridized polypropylene fibre (PF)-macro steel fibre (MSF) can improve the mechanical and ductility characteristics of concrete. PF-MSF hybrid fibers are more effective in arresting cracks macro/micro than a single fiber type. This study aims to examine the effect of the PF-MSF hybrid fibres on the compressive toughness characteristics of fibre-reinforced concrete (FRC) to identify the fibers' optimized mixture proportion. To this end, the effect of the PF, MSF, and PF-MSF hybrid fibres on the density, water absorption, and voids in concrete hardened, compressive strength, compressive toughness, and toughness index of FRC has been also examined. The conducted comparison of the above-mentioned properties between the prepared specimens with the variables involves different PF ratios, including (0%, 0.1%, 0.175, 0.25%, 1.0%) and MSF (0%, 0.75, 0.825, 0.9%, 1.0%), by volume. The experimental results showed that hybrid FRC achieved more significant improvements in compressive toughness characteristics compared with mono MSFs or PFs inclusion. The reinforced specimen with 0.1% PF-0.9% MSF hybrid FRC has accomplished higher compressive toughness of approximately 0.321 MPa, i.e., 106.5% higher than that of the controlled mix. More importantly, the most significant improvement in compressive strength with increasing density and reducing water absorption and voids has been observed for the hybrid mixture of 0.1% PF-0.9% MSF. This work on hybrid fiber-reinforced concrete is believed to provide useful insights into a more thorough understanding of the influence of hybrid fiber on concrete.